Immunity and growth of freshwater prawn fed with dietary β-glucan supplementation - Ekasari, Julie; Napitupulu, Jhon Lamhot F.; Surawidjaja, Enang Harris (Indonesian Society of Scientific Aquaculture (ISSA), 2016)
ABSTRACT Freshwater prawn Macrobrachium rosenbergii is one of the most important aquaculture commodities in Indonesia. This study evaluated the effect of dietary β-glucan supplementation (0%, 0.075%, 0.15%, and 0.225%) on the immune parameters, survival, and growth of giant freshwater prawn. Prawn juvenile with an initial body weight of 1.25±0.041 g was randomly distributed into eight units of glass aquaria (150 L) with a density of 16 animals/aquarium. Phenoloxydase activity, total and differential haemocyte counts, survival, and specific growth rate of the prawn were measured and calculated on the final day of experiment (day 42). Phenoloxydase activity, total and differential haemocyte counts of β-glucan treatments were higher than control, whereas no significant difference was observed in survival. The highest specific growth rate was observed in the 0.15% β-glucan supplementation treatment with 1.92%/day. Keywords: phenoloxydase activity, haemocyte, β-glucan, specific growth rate, giant freshwater prawn ABSTRAK Udang galah Macrobrachium rosenbergii merupakan salah satu komoditas akuakultur yang penting di Indonesia. Penelitian ini dilakukan untuk mengevaluasi pengaruh suplementasi pakan dengan β-glukan sebesar 0%, 0,075%, 0,15%, dan 0,225% terhadap parameter imunitas dan kinerja pertumbuhan udang galah. Juvenil udang dengan bobot tebar rata-rata 1,25±0,041 g ditebar secara acak pada delapan unit akuarium (150 L) dengan padat tebar 16 ekor/akuarium. Parameter yang diamati adalah aktivitas fenoloksidase (PO), jumlah dan diferensiasi hemosit, sintasan, dan laju pertumbuhan spesifik yang diukur dan dihitung setelah 42 hari masa pemeliharaan. Hasil penelitian menunjukkan bahwa nilai aktivitas PO, total hemosit, dan diferensial hemosit pada udang yang diberi pakan dengan suplementasi β-glukan cenderung lebih tinggi dibandingkan dengan kontrol. Sintasan masing-masing perlakuan tidak berbeda nyata dengan perlakuan kontrol. Laju pertumbuhan spesifik tertinggi terdapat pada perlakuan β-glukan 0,15% sebesar 1,92%/hari. Kata kunci: aktivitas phenoloxydase, hemosit, β-glukan, udang galah, laju pertumbuhan spesifik